Older Public Housing Tenants’ Capabilities for Physical Activity Described Using Walk-Along Interviews in Montreal, Canada - Kadia Saint-Onge (MDPI AG, 2021)
Older public housing tenants experience various factors associated with physical inactivity and are locally dependent on their environment to support their physical activity. A better understanding of the person-environment fit for physical activity could highlight avenues to improve access to physical activity for this subgroup of the population. The aim of this study was to evaluate older public housing tenants’ capabilities for physical activity in their residential environment using a socioecological approach. We conducted individual semi-structured walk-along interviews with 26 tenants (female = 18, male = 8, mean age = 71.96 years old). Living in housing developments exclusively for adults aged 60 years or over in three neighborhoods in the city of Montreal, Canada. A hybrid thematic analysis produced five capabilities for physical activity: Political, financial, social, physical, and psychological. Themes spanned across ecological levels including individual, public housing, community, and government. Tenant committees appear important to physical activity promotion. Participants called for psychosocial interventions to boost their capability for physical activity as well as greater implication from the housing authority and from government. Results further support a call for intersectoral action to improve access to physical activity for less affluent subgroups of the population such as older public housing tenants.